Pelayanan Misi Mahasiswa STT Ebenhaezer kepada Masyarakat Suku Enim Menggunakan Paradigma Misi David J. Bosc - Febriaman Lalaziduhu Harefa; Jeane Paath; David Baluseda (Sekolah Tinggi Teologi Kalimantan, 2022)
This study examines the mission of STT Ebenhaezer students to the indigenous people of the Enim tribe, South Sumatra. In the last decade it has experienced setbacks caused by several factors. To provide solutions to the above problems, field research was carried out using a qualitative case study approach using David J. Bosc's mission theory study. The result is that STT Ebenhaezer students must build mission motivation based on the Bible, in serving and reaching the indigenous people of the Enim tribe, STT Ebenhaezer students try to collaborate with educational institutions, foundations, and churches to create holistic, constructive, and contextual mission service programs, students build mission communication with a contextualization approach, inculturation of the culture of the Enim tribe, students become solution makers on social issues that are currently developing and have an impact on the lives of the indigenous people of the Enim tribe directly and STT Ebenhaezer as an educational institution trying to digitize services. This research will make a direct contribution to achieving the vision and mission of STT Ebenhaezer and maximizing cross-cultural services for STT Ebenhaezer students, especially in reaching out to the Enim-South Sumatra ethnic community.Penelitian ini mengkaji doing mission mahasiswa STT Ebenhaezer kapada masyarakat adat suku Enim Sumatera Selatan. Dimana dalam dekade terakhir ini mengalami kemunduran yang disebabkan oleh beberapa faktor. Untuk memberikan solusi terhadap masalah di atas, maka diadakan penelitian lapangan dengan pendekatan kualitatif metode studi kasus dengan menggunakan kajian teori misi David J Bosc. Hasilnya adalah mahasiswa STT Ebenhaezer harus membangun motivasi misi berdasarkan Alkitab, dalam melayani dan menjangkau masyarakat adat suku Enim, mahasiswa STT Ebenhaezer berusaha menjalin kerja sama dengan lembaga-lembaga pendidikan, yayasan dan gereja-gereja untuk membuat program pelayanan misi holistik, konstruktif dan kontekstual, mahasiswa membangun komunikasi misi dengan pendekatan kontekstualisasi, inkulturisasi budaya suku Enim, mahasiswa menjadi solution maker terhadap isu-isu sosial yang sedang berkembang dan berdampak dalam kehidupan masyarakat adat suku Enim secara langsung dan STT Ebenhaezer sebagai lembaga pendidikan berusaha melakukan digitalisasi dalam pelayanan. Penelitian ini akan memberikan kontribusi langsung kepada pencapaian visi dan misi STT Ebenhaezer dan memaksimalkan pelayanan lintas budaya mahasiswa STT Ebenhaezer khususnya dalam menjangkau masyarakat suku Enim-Sumatera Selatan.